Perbedaan Skor Nyeri pada Anak dengan Pemberian Madu Setelah Dilakukan Tindakan Pemasangan Infus - Sintiya Halisya Pebriani; Irwadi Irwadi (Jurnal Kesehatan, 2018)
Intravenous fluid therapy in a child in the emergency room may lead to prolonged trauma and is a procedure that can cause anxiety, fear and uncomfortable pain. Handling of pain in children can be done with non-pharmacological techniques that are by giving a sweet taste of honey, wherein honey contains flavonoid content that can inhibit the pain. The purpose of this study was to know differences in pain scores after the installation of infusion between groups of children given honey and not given honey. The research design used in the form of quasi-experiment with nonequivalent control group type, post-only design, with the number of samples were 34 people who met the inclusion criteria. The sample was divided into two groups: the intervention group who received honey peroral (17 respondents) and the control group who did not get honey peroral (17 respondents), with age of respondent 1-6 years. Pain scores were evaluated with Children's Hospital of the Eastern Ontario Pain Scale (CHEOPS). A statistical test was using Mann-Whitney test with 95% (α=0,05 ) incidence rate. The result showed that there was a difference in child pain score in intervention group and control group with p-value=0.000. It can be concluded that there was an effect of giving honey to pain score, wherein the intervention group the pain score was lower than the control group, meaning that honey can reduce the pain response in children.